SISTEM INFORMASI TUGAS AKHIR BERBASIS WEB (Studi Kasus: Sekolah Tinggi Teknologi Ronggolawe Cepu) - Erviana -; Joko Handoyo (SIMETRIS, 2017)
The final project is a scientific paper compiled by every final semester student to obtain a bachelor degree or three diploma basedon the problem or research as a graduation requirement in accordance with their respective fields. The process of final project guidance atRonggolawe High School of Engineering (STTR) Cepu which is still manual causing the students difficulties in face-to-face directly with thesupervisor or head of study program because of the timing of the less precise or less effective and there is no system information finalproject, Data has not been stored neatly.To overcome these problems it is necessary to design an Online Task Information System on High School Engineering Ronggolawe(STTR) Cepu. Online final project system to facilitate students in the process of making the final project.The author solve the problem using life cycle system (SDLC) method with waterfall model. The development of this system includesthe process of submitting the title made by the students to the head of study program, proposal guidance process and final report on thesupervisor. The result of the functionality test of the final assignment information system is considered feasible in terms of functionality, with100% result in black box testing for testing of sub-characteristics of suitability and accurancy. It is expected that this system can help thestudents in the final task guidance process to be more efficient and better.